Higher blood urea nitrogen level is independently linked with the presence and severity of neonatal sepsis. (1st January 2021) - Li, Xiaojuan; Li, Tiewei; Wang, Jingjing; Dong, Geng; Zhang, Min; Xu, Zhe; Hu, Yidi; Xie, Bo; Yang, Junmei; Wang, Yuewu
Abstract: Background: Previous studies have demonstrated that blood urea nitrogen (BUN) is strongly associated with sepsis. However, no data are currently available regarding the association of BUN levels and neonatal sepsis. Thus, this study aimed to investigate the role of BUN in predicting the presence and severity of neonatal sepsis. Methods: In this study, we enrolled 925 neonates. Among them, 737 neonates were diagnosed with sepsis, including 426 neonates with severe sepsis. Neonates with hyperbilirubinemia ( n  = 188) served as controls. We collected complete clinical and laboratory data were collected. Multivariate logistic regression analysis was performed to identify the potential independent risk factor for neonatal sepsis. Receiver operating characteristic (ROC) curve analysis was used to evaluate the prediction accuracy of BUN in predicting neonatal sepsis. All statistical analyses were performed using the statistical package SPSS 24.0. Results: Neonates with sepsis and severe sepsis had a higher level of BUN. The prevalence of neonates with severe sepsis was dramatically increased according to BUN tertiles. Correlation analysis showed that BUN levels were positively correlated with the levels of infection marker procalcitonin (PCT) and high-sensitivity C-reactive protein (hsCRP). Multiple logistic regression analysis showed that BUN was an independent risk factor for the presence and severity of neonatal sepsis. ROC curve analysis showed that BUN had a well discriminatory power in predicting sepsis (area under curve (AUC) = 0.69, 95% CI, 0.66–0.74, p  < .001) and severe sepsis (AUC = 0.72, 95% CI, 0.67–0.78, p  < .001). Conclusion: Higher BUN level is independently linked with the presence and severity of neonatal sepsis.